Missional Small Groups Becoming a Community That Makes a Difference in the World. - Boren, M. Scott (Grand Rapids : Baker Publishing Group, 2010)
Missional think tank Allelon reenvisions the small groups movement through a book by the leading voice in missional communities.
Appendix C: The Role Of A Pastor, Coach, Or Elder In Developing Missional Small Groupsnotes.
Description based upon print version of record.
Keywords: Church group work; Mission of the church; Small groups -- Religious aspects -- Christianity; Electronic books